2023
DOI: 10.31234/osf.io/xta3y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychosocial Interventions for Children and Adolescents with Conduct Problems

Natalie Goulter,
Georgette E. Fleming

Abstract: Conduct problems (CP) encompass antisocial behaviors that violate others’ rights and/or societal norms. In this chapter, we describe evidence-based psychosocial interventions targeting CP during childhood and adolescence. Specifically, we outline the theoretical underpinnings and intervention components of family-based interventions and multicomponent interventions, including interventions specifically targeting high-risk personality traits for conduct problems (e.g., callous-unemotional traits and psychopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Emerging decomposition research on mechanisms of intervention-related change found that approximately a third of FT's impact on antisocial outcomes was accounted for by improvements in both social and self-regulation skills (including prosocial behavior, emotion regulation, and problem-solving; Sorensen et al, 2016). Compared to research on moderators (Goulter & Fleming, 2023;McMahon et al, 2021), much less work has been conducted investigating mechanisms of change. Further research is needed testing theoretical mechanisms of action, and the cascading effects of these mechanisms on change in impulsivity and change in other constructs, such as conduct problems, seems of prime interest.…”
Section: Impulsivity Profile Comparisons On Predictors and Adult Outc...mentioning
confidence: 99%
“…Emerging decomposition research on mechanisms of intervention-related change found that approximately a third of FT's impact on antisocial outcomes was accounted for by improvements in both social and self-regulation skills (including prosocial behavior, emotion regulation, and problem-solving; Sorensen et al, 2016). Compared to research on moderators (Goulter & Fleming, 2023;McMahon et al, 2021), much less work has been conducted investigating mechanisms of change. Further research is needed testing theoretical mechanisms of action, and the cascading effects of these mechanisms on change in impulsivity and change in other constructs, such as conduct problems, seems of prime interest.…”
Section: Impulsivity Profile Comparisons On Predictors and Adult Outc...mentioning
confidence: 99%